The use of secure anonymised data linkage to determine changes in healthcare utilisation following severe open tibial fractures. Issue 7 (July 2015) - Page, Piers R.J.; Trickett, Ryan W.; Rahman, Shakeel M.; Walters, Angharad; Pinder, Leila M.; Brooks, Caroline J.; Hutchings, Hayley; Pallister, Ian
Abstract Severe open fractures of the lower limbs are complex injuries requiring expert multidisciplinary management in appropriate orthoplastic centres. This study aimed to assess the impact of open fractures on healthcare utilisation and test the null hypotheses that there is no difference in healthcare utilisation between the year before and year after injury, and that there is no difference in healthcare utilisation in the year post-injury between patients admitted directly to an orthoplastic centre in keeping with the joint BOA/BAPRAS standards and those having initial surgery elsewhere. This retrospective cohort study utilising secure anonymised information linkage (SAIL), a novel databank of anonymised nationally pooled health records, recruited patients over 18 years of age sustaining severe open lower limb fractures managed primarily or secondarily at our centre and who had data available in the SAIL databank. 101 patients met inclusion criteria and 90 of these had records in the SAIL databank. The number of days in hospital, number of primary care attendances, number of outpatient attendances and number of emergency department attendances in the years prior and subsequent to injury were recorded. Patients sustaining open fractures had significantly different healthcare utilisation in the year after injury when compared with the year before, in terms of days spent in hospital (23.42 vs. 1.70, p = 0.000), outpatient attendances (11.98 vs. 1.05, p = 0.000), primary care attendances (29.48 vs. 11.99, p = 0.000) and emergency department presentations (0.2 vs. 0.01, p = 0.025). Patients admitted directly to orthoplastic centres had significantly fewer operations (1.78 vs. 3.31) and GP attendances (23.6 vs. 33.52) than those transferred in subsequent to initial management in other units. There is a significant increase in healthcare utilisation after open tibial fracture. Adherence to national standards minimises the impact of this on both patients and health services.